1989
DOI: 10.1164/ajrccm/140.5.1237
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Hemodynamics and Gas Exchange in Patients with Chronic Obstruction Pulmonary Disease, Sleep Desaturation, and a Daytime PaO2above 60 mm Hg

Abstract: Nocturnal oxyhemoglobin desaturation (NOD) has been reported in patients with disease of the pulmonary parenchyma and/or chest wall. The resulting hypoxemia could play a role in the development of pulmonary hypertension. We have previously demonstrated a small but statistically significant difference in resting pulmonary artery pressure (Ppa) and pulmonary vascular resistance (PVR) between two groups of patients with COPD of similar age, symptomatology, and degree of pulmonary dysfunction. These two groups wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 1 publication
1
30
2
2
Order By: Relevance
“…Exercising Ppa, measured in 54 patients, was also similar in the two groups, in contrast to the results of FLETCHER et al [29]. Furthermore, Ppa was not significantly correlated with the mean nocturnal Sa,O 2 nor with t Sa,O 2 <90%.…”
Section: Nocturnal Desaturation and Daytime (Permanent) Pulmonary Hypcontrasting
confidence: 54%
“…Exercising Ppa, measured in 54 patients, was also similar in the two groups, in contrast to the results of FLETCHER et al [29]. Furthermore, Ppa was not significantly correlated with the mean nocturnal Sa,O 2 nor with t Sa,O 2 <90%.…”
Section: Nocturnal Desaturation and Daytime (Permanent) Pulmonary Hypcontrasting
confidence: 54%
“…In advanced COPD, patients with resting PH have a marked increase in Ppa during steady-state exercise [42,65,66]: a COPD patient whose baseline P pa is modestly elevated (25-30 mmHg) may exhibit severe PH (50-60 mmHg) during moderate exercise (30-40 W). This is explained by the fact that PVR does not decrease during exercise in advanced COPD patients [65,66], whereas it does in healthy subjects; as cardiac output is doubled for this level of exercise, P pa increases by ,100%.…”
Section: Natural History Of Ph In Copd Exercising Phmentioning
confidence: 99%
“…This is explained by the fact that PVR does not decrease during exercise in advanced COPD patients [65,66], whereas it does in healthy subjects; as cardiac output is doubled for this level of exercise, P pa increases by ,100%. From a practical viewpoint, this means that daily activities, such as climbing stairs, or even walking, can induce marked PH.…”
Section: Natural History Of Ph In Copd Exercising Phmentioning
confidence: 99%
“…Pulmonary arterial vasoconstriction secondary to hypoxia may cause pulmonary arterial hypertension but there appears to be significant inter-individual differences in such a response [95][96][97]. In a study by Held et al, a cohort of 18 patients were identified to have with pulmonary hypertension and hypoventilation [68].…”
Section: Long Term Effects Mortality and Prognosis Of Pap Therapymentioning
confidence: 99%